A Multiyear CONUS‐Wide Analysis of Lightning Strikes to Wind Turbines - Ryan Said; Eric Grimit; Martin Murphy (Wind Energy)
ABSTRACT Lightning strikes to wind turbines (WTs) pose significant hazards and operational costs to the renewable wind industry. These strikes fall into two categories: downward cloud‐to‐ground (CG) strokes and upward discharges, which can be self‐initiated or triggered by a nearby flash. The incidence of each type of strike depends on several factors, including the electrical structure of the thunderstorm and turbine height. The strike rates of CG strokes and triggered upward lightning can be normalized by the amount of local lightning activity, where the constant of proportionality carries units of area and is often termed the collection area. This paper introduces a statistical analysis technique that uses lightning locating system (LLS) data to estimate the collection areas for downward and triggered upward lightning strikes to WTs. The technique includes a normalization method that addresses the confounding factor of neighboring WTs. This analysis method is applied to 7 years of data from the National Lightning Detection NetworkTM and the US WT Database to investigate the dependence of collection areas on blade tip height. The results are compared against estimates of collection areas derived from counts of LLS‐detected CG strokes close to WTs.